The Association Between Fatalism and Mammography Use in Korean American Immigrant Women. (August 2022) - Lee, Mi Hwa; Hong, Saahoon; Merighi, Joseph R.
Fatalism is reported as a salient cultural belief that influences cancer screening disparities in racial and ethnic minority groups. Previous studies provide a range of measures and descriptions of cancer fatalism, but no studies to our knowledge have analyzed how fatalistic views cluster together within subgroups to form distinct profiles, and how these profiles can be predicted. This study identified subgroups of Korean American immigrants with similar fatalistic beliefs toward cancer and examined the influence of fatalism, health belief variables, and health literacy on mammography use. A cross-sectional survey design was used to obtain a convenience sample of 240 Korean American immigrant women in Los Angeles, California. Latent class analysis was used to identify unobserved subgroups of fatalism. Hierarchical logistic regression models were used to identify predisposing, enabling, and need factors associated with recent mammography use. The latent class analysis model identified three cancer fatalism subgroups: high fatalism (17.8%), moderate fatalism (36.7%), and low fatalism (45.5%). Women in the high fatalism subgroup were more likely to have had a mammogram within the past 2 years than women in the low fatalism subgroup. Regression analysis revealed three facilitators of recent mammogram use: level of fatalism, perceived barriers to mammogram, and family history of cancer. Although cultural beliefs can have a powerful influence on health-seeking behavior, it is important to weigh individual and contextual factors that may weaken or mediate the relationship between fatalism and engaging in preventive care such as having a mammogram.